Evaluating Rainfall Effects on Soil Parameters and Slope Stability Using Hydrology Procedure (HP26) - Omar, Heryanti Awang; Nasir, Nur Fazielah; Rosly, Mohammad Haziq; Mohamad, Habib Musa; Majain, Nelly; Afizah Asman, Nurul Shahadahtul (Civil Engineering Journal, 2026)
Rainfall-induced slope failures are a major geohazard in tropical regions, often triggered by intense or prolonged rainfall that alters soil strength and pore water pressure conditions. This study evaluates the effects of rainfall duration on slope stability in Kota Belud and Ranau, Sabah, by applying Hydrology Procedure 26 (HP26) rainfall data with numerical modelling using SEEP/W and SLOPE/W under the Limit Equilibrium Method (LEM). Soil parameters were derived from site investigations, with strength values including cohesion (0.5-9.7 kPa) and friction angle (25.7°-30°). The results showed that short-duration rainfall (1 hour) had minimal impact on stability, while prolonged (24-hour) rainfall significantly increased pore water pressure, reducing the factor of safety (FOS) by 25-30%. A localized weak zone in Ranau was identified, with cohesion decreasing from 7 kPa to 5 kPa between 7.4 m and 13.5 m depth, corresponding to potential slip surfaces. Findings align with previous research on infiltration-driven failures, but this study demonstrates the practical use of HP26 rainfall design data for tropical slope analysis. The novelty lies in linking rainfall duration, soil-water interactions, and FOS reduction through a standardized rainfall procedure, providing a framework for improved slope risk assessment in rainfall-prone terrains.